Pengaruh Terapi Emotional Freedom Technique(EFT) Terhadap Pencegahan PostpartumBlues Pada Ibu Pasca Melahirkan di Wilayah Kerja Puskesmas Cahya Maju Kecamatan Lempuing - Zukhruf, Meita Robbiatul; Itriyah (Program Studi Tasawuf dan Psikoterapi, 2024)
The lack of knowledge about postpartum blues among postpartum mothers in the Puskesmas Cahya Maju. This lack of awareness leads to many mothers not recognizing the symptoms of postpartum blues and potentially worsening their condition. The research problem is the need for prevention methods for postpartum blues in postpartum mothers. The aim of the study is to investigate the effectiveness of the Emotional Freedom Technique (EFT) as a self-administered therapy for postpartum blues. The methodology used in this study is the EFT therapy, which utilizes the body's meridian points to address energy imbalances that contribute to psychological effects. EFT is a branch of energy psychology that aims to improve mental, emotional, and behavioral conditions by addressing imbalances in the body's energy system. The participants in this study are postpartum mothers who are experiencing symptoms of postpartum blues. The therapy is self-administered by the mothers at home without the assistance of a therapist. The results of the study show that EFT therapy is effective in reducing symptoms of postpartum blues in postpartum mothers. The therapy helps restore balance to the body's energy system, which in turn improves the chemical balance in the brain and emotional state. This finding has important implications for the prevention and management of postpartum blues in postpartum mothers.The study highlights the importance of raising awareness about postpartum blues and providing prevention methods for postpartum mothers. The use of EFT therapy as a self-administered treatment option offers a convenient and effective approach for postpartum mothers to manage their symptoms.